Pengaruh Brand Image dan Word Of Mouth Terhadap Keputusan Pembelian Produk Kosmetik Wardah : Studi Kasus Pada Mahasiswi Fakultas Ekonomi dan Bisnis Islam UIN Raden Fatah Palembang - Salsabila Salsabila; Hilda Hilda; Nur Hesthria (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The aim of this research is to determine the influence of brand image and word of mouth on purchasing decisions for wardah cosmetic products among students at the Faculty Of Islamic Economics and Business at UIN Raden Fatah Palembang. The type of research used is quantitative research. The data analysis techniques used in this research are validity and reliability testing, classical assumption testing and hypothesis testing. The research result show that brand image has a positive and significant effect on purchasing decisions, word of mouth has a positive and significant effect on purchasing decision. Brand image and Word of mouth simultaneously have a positive and significant effect on purchasing decisions.